Dynamics of a fin driven boat - modeling and simulation - Tran, H. T.; Bikowski, S.; Wolf, C. D.; Maiber, P. (Vietnam Journal of Mechanics, 2003)
In this paper the motion of a small sport boat running on a lake is simulated using alaska tools when the external forces and torques from water and excitation force from a person are applied. Using the results from measurements we have done some validations.